The influence of liposome-mediated APOE3 gene transfection in brain cells on exploratory behavior and emotionality of rats after experimental traumatic brain injury - Biloshytsky, V. V.; Velichko, O. M.; Gridina, N. Ya.; Tsyba, L. O.; Pedachenko, E. G. (Ukrainian Neurosurgical Journal, 2010)
The goal of study was to estimate in the experiment the levels of exploratory behavior and emotionality disorders of rats with severe diffuse traumatic brain injury (TBI), and also possibilities of such disorders correction using gene therapy that launches Е3 synthesis in brain tissue — isoform of apolipoprotein E. Severe diffuse TBI in rats was inflicted under overall anesthesia by free load weighting 450 g, falling from 1.5 m height. The mixture of DOTAP liposome and 25 µg of plasmid vector pCMV•SPORT6 with cDNA of APOE3 gene was infused intraventricularly using ALZET osmotic pumps. The exploratory behavior and emotionality of rats in experimental and control groups were studied in open field test 7 days after trauma. The obtained results demonstrated that severe diffuse TBI in rats was characterized by evolution of evident exploratory behavior and emotionality disorders that reflected stress and anxiety increasing. The liposome-mediated brain tissue transfection with plasmid vector carrying the gene of apolipoprotein E Е3 isoform caused regress of posttraumatic exploratory behavior and emotionality disorders and recovery of affected functions.